2021
DOI: 10.1155/2021/6056636
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Active Components and Key Targets of Radix Codonopsis in the Treatment of Gastric Cancer

Abstract: Gastric cancer is the fifth most common cancer type in the world. The incidence and mortality of gastric cancer in China ranks second among malignant tumors in the country. At present, the main treatment method of gastric cancer is still surgical resection combined with chemotherapy. However, chemotherapy drugs will cause serious toxic and side effects on other normal tissues and cells. At the same time, chemotherapy drugs can make patients develop drug resistance and seriously affect the curative effect. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Although luteolin, capsaicin, and sulforaphane are not the most abundant ingredients of Codonopsis pilosula , they are essential for understanding the pharmacological effects of Codonopsis pilosula . Tang et al found that Codonopsis pilosula may play an antigastric cancer role through luteolin [ 54 ], suggesting that luteolin may play an important role in the anticancer effects of Codonopsis pilosula . Furthermore, several studies showed that luteolin [ 55 ], capsaicin [ 56 ], and sulforaphane [ 57 ] could target HMOX1 and significantly enhance its expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Although luteolin, capsaicin, and sulforaphane are not the most abundant ingredients of Codonopsis pilosula , they are essential for understanding the pharmacological effects of Codonopsis pilosula . Tang et al found that Codonopsis pilosula may play an antigastric cancer role through luteolin [ 54 ], suggesting that luteolin may play an important role in the anticancer effects of Codonopsis pilosula . Furthermore, several studies showed that luteolin [ 55 ], capsaicin [ 56 ], and sulforaphane [ 57 ] could target HMOX1 and significantly enhance its expression level.…”
Section: Discussionmentioning
confidence: 99%
“…124,125 Codonopsis lanceolata also has the effects of anti-inflammation, relieving cough, anti-microbial, liver protection, skin whitening, anti-obesity effect. [126][127][128][129]…”
Section: Othersmentioning
confidence: 99%
“…In addition, Radix Codonopsis also has the effects of anti‐fatigue and anti‐stress 123 anti‐radiation, anti‐inflammation, analgesic action, strengthening uterine contractions, strengthening the function of reticuloendothelial system 124,125 . Codonopsis lanceolata also has the effects of anti‐inflammation, relieving cough, anti‐microbial, liver protection, skin whitening, anti‐obesity effect 126–129 …”
Section: Pharmacologymentioning
confidence: 99%
“…Codonopsis pilosula , a perennial herb of the Campanulaceae family, is a traditional Chinese herb that is rich in bioactive compounds including polyacetylene, polyene, flavonoids, lignans, alkaloids, coumarins, terpenes, steroids, organic acids, and polysaccharides [ 1 ]. C. pilosula is widely used in the therapy of hyperlipidemia, asthma, bronchitis, tuberculosis, and dyspepsia [ 2 ], and also plays a key role in boosting the body’s immunity [ 3 ], reducing blood glucose [ 4 ], promoting hematopoiesis [ 5 ], protecting the cardiovascular system [ 6 ], repairing damaged nerve cells, and regulating gastrointestinal function [ 7 ].…”
Section: Introductionmentioning
confidence: 99%